To Leave or to Stay in the Current Organization After an MBA - Supangco, Vivien T. (Philippine Management Review, 2014)
This study looked into the factors that would make employees likely to remain in their organizations. It used social exchange and human capital theories and the side-bet hypothesis to guide the development of hypotheses. The study employed a systematic random sampling with a random start, with a total of 76 respondents out of the 286 MBA students enrolled at the University of the Philippines in school year 2010-11. To address the research question, a logistic regression analysis was used. Results showed that the likelihood of staying in an organization increases with perceived organizational support and career satisfaction, but decreases with ability. Organizations can increase employees’ likelihood of staying by providing benefits and opportunities that employees perceive as concern for their well-being. Moreover, the ease of movement by high ability individuals makes them a critical target group in an organization’s retention management efforts. Together, the findings suggest a holistic picture of intention to leave by including human capital factors, such as investment in the organization and ability, in addition to relational and attitudinal factors that are commonly used in turnover studies, such as job dissatisfaction and organizational support. However, the use of MBA students in one university and the indirect measurement of ability limit generalizability of results. Future research can assess its effects using direct measures and further study the null result of investment in organization.
Keywords: career satisfaction, organizational support, investment in organization, ability, MBA careers, turnover, intention to stay, Philippines